Return of individual research results from genomic research: a systematic review of stakeholder perspectives - Vears, Danya F.; Minion, Joel T.; Roberts, Stephanie J.; Cummings, James; Machirori, Mavis; Blell, Mwenza; Budin-Ljøsne, Isabelle; Cowley, Lorraine; Dyke, Stephanie O. M.; Gaff, Clara; Green, Robert; Hall, Alison; et al. (PLOS ONE, 2021)
Despite the plethora of empirical studies conducted to date, debate continues about whether and to what extent results should be returned to participants of genomic research. We aimed to systematically review the empirical literature exploring stakeholders’ perspectives on return of individual research results (IRR) from genomic research. We examined preferences for receiving or willingness to return IRR, and experiences with either receiving or returning them. The systematic searches were conducted across five major databases in August 2018 and repeated in April 2020, and included studies reporting findings from primary research regardless of method (quantitative, qualitative, mixed). Articles that related to the clinical setting were excluded. Our search identified 221 articles that met our search criteria. This included 118 quantitative, 69 qualitative and 34 mixed methods studies. These articles included a total number of 118,874 stakeholders with research participants (85,270/72%) and members of the general public (40,967/35%) being the largest groups represented. The articles spanned at least 22 different countries with most (144/65%) being from the USA. Most (76%) discussed clinical research projects, rather than biobanks. More than half (58%) gauged views that were hypothetical. We found overwhelming evidence of high interest in return of IRR from potential and actual genomic research participants. There is also a general willingness to provide such results by researchers and health professionals, although they tend to adopt a more cautious stance. While all results are desired to some degree, those that have the potential to change clinical management are generally prioritized by all stakeholders. Professional stakeholders appear more willing to return results that are reliable and clinically relevant than those that are less reliable and lack clinical relevance. The lack of evidence for significant enduring psychological harm and the clear benefits to some research participants suggest that researchers should be returning actionable IRRs to participants.